Peran Manajemen Asrama Al-Nur dalam Pembinaan Akhlak Santri Madrasah Aliyah (MA) Ma’had Al-Zaytun - Ula Muvida Toyiba; Sobirin Sobirin; Meity Suryandari (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
This thesis examines the role of dormitory management in fostering the morals of Madrasah Aliyah students where they are teenagers. One of the problems often encountered by dormitory management on the behavior of students is the discovery of items that should not be brought in the pesantren and some behaviors that do not reflect good morals to teachers, elders and peers. The purpose of this study is to identify the role of Al-Nur dormitory management in helping to foster the morals of students and to find out the supporting factors and inhibiting factors in fostering the morals of students. This research method uses a descriptive qualitative approach that examines individual experiences to tell their personal experiences about the role of management and the moral development model carried out. Data collection procedures carried out are interviews, observation and documentation. The results showed that the management of Al-Nur dormitory plays an important role in shaping the morals of students through various programs. Good management includes effective planning, organizing, implementing, and supervising. There are supporting factors in moral development including cooperation, exemplary, and self-motivation. However, there are also inhibiting factors such as the variety of santri activities, internal problems, and self-awareness.